Risk Assessment of WtE Plants by Using a Modified Fuzzy SCEA Approach - Ilbahar, Esra; Cebi, Selcuk; Kahraman, Cengiz (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
With the increasing sustainability concerns, energy production from waste has also come to the fore as well as recycling and reuse. Since there are various materials processed by waste to energy (WtE) plants and several types of equipment used in different processes, there are different sources of risks in these plants. It is important to determine and prioritize these risks in order to effectively manage them by taking the necessary precautions. However, the risk evaluation process mostly depends on expert judgments which contain uncertainty. Therefore, in this study, after risks in a WtE plant are categorized, interval-valued intuitionistic fuzzy (IVIF) analytic hierarchy process (AHP) is used to obtain probability, severity, frequency, and detectability weights of these risks. Then, the risks are prioritized by using these weights in safety and critical effect analysis (SCEA). It was revealed that the most critical risk is inappropriate storage of waste load , followed by heat generated by failing bearings on various plant items and the dust generated when processing and sizing waste material.
Keywords: Risk assessment; Waste to energy plant; Intuitionistic fuzzy sets; AHP; Rule-based system; WASTE; INCINERATION; EMISSIONS; SAFETY; HEALTH; CHINA; Computer Science